2014
DOI: 10.1177/0013916514554695
|View full text |Cite
|
Sign up to set email alerts
|

Unearthing the “Green” Personality

Abstract: Pro-environmental attitudes and behaviors show substantial individual differences, and exploring their predictors can help reveal the origins of pro-environmental behavior. Basic personality traits may provide a partial explanation, but it is unclear which personality traits are reliably associated with pro-environmental behaviors. This article uses a specific type of environmental behavior, reducing greenhouse gas emissions, to clarify which personality correlates are most robustly associated with behavior, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
106
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(125 citation statements)
references
References 44 publications
13
106
1
5
Order By: Relevance
“…As a side note, our analyses revealed some exploratory findings regarding broader personality correlates of pro-environmental behaviour. Along the lines of previous research (Brick & Lewis, 2016;Busic-Sontic et al, 2017;Hilbig et al, 2013;Lee et al, 2015;Markowitz et al, 2012;Ojedokun, 2018;Terrier et al, 2016), openness to experience was found to be the Big Five trait most closely linked to self-reported pro-environmental behaviour in our study. Our data further suggest, for the first time, that this relationship also extends to an objective measure of actual proenvironmental behaviour (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As a side note, our analyses revealed some exploratory findings regarding broader personality correlates of pro-environmental behaviour. Along the lines of previous research (Brick & Lewis, 2016;Busic-Sontic et al, 2017;Hilbig et al, 2013;Lee et al, 2015;Markowitz et al, 2012;Ojedokun, 2018;Terrier et al, 2016), openness to experience was found to be the Big Five trait most closely linked to self-reported pro-environmental behaviour in our study. Our data further suggest, for the first time, that this relationship also extends to an objective measure of actual proenvironmental behaviour (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, both measures of pro-environmental behaviour were related to agreeableness, a correlation that has been found in some (e.g. Brick & Lewis, 2016) but not all (e.g. Markowitz et al, 2012) previous personality studies.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, three hypotheses (i.e., H3, H5, and H6) had been rejected in this study. Firstly, while emotional stability was regarded as a key factor in the big five personality traits of pro-environmental behavior [39][40][41][42][43][44], the findings in this study did not uncover any positive relationship between emotional stability and pro-environmental behavior (H3). Instead, emotional stability could influence pro-environmental behavior through internal locus of control.…”
Section: Discussionmentioning
confidence: 64%
“…They are patient, self-contentment, deliberative, unenvious, strong-minded, and objective [35][36][37]. Although emotional stability is an emotion-based characteristic that is considered unrelated to cognition-based values [38], studies have shown that among the big five personality traits, it is a key factor affecting pro-environmental behavior [39][40][41][42][43][44]. Previous studies reveal that personality traits may change because of a person's life learning experience, and as a result become more cautious, reliable, and knowledgeable [45].…”
Section: Introductionmentioning
confidence: 99%
“…For example, personal climate change norms are positively associated with two moral values (care and fairness) and negatively associated with another (authority, Feinberg andWiller 2013, Jansson andDorrepaal 2015). Aspects of personality (extraversion, conscientiousness, and openness) have been associated with attitudes and selfreported behaviors pertaining to the environment (Milfont andSibley 2012, Brick andLewis 2016).…”
Section: Introductionmentioning
confidence: 99%